Neohesperidin Ameliorates Steroid-Induced Osteonecrosis of the Femoral Head by Inhibiting the Histone Modification of lncRNA HOTAIR - Yuan S; Zhang C; Zhu Y; Wang B (Dove Medical Press, 2020)
Shuai Yuan,* Chuanxin Zhang,* Yunli Zhu, Bo Wang Department of Joint Surgery and Sports Medicine, Changzheng Hospital, Naval Medical University, Shanghai, People’s Republic of China*These authors contributed equally to this workCorrespondence: Bo WangDepartment of Joint Surgery and Sports Medicine, Changzheng Hospital, Naval Medical University, No. 415, Fengyang Road, Huangpu District, Shanghai 200003, People’s Republic of ChinaTel +86-21-81885639Email wangbo_wbob@163.comBackground: Neohesperidin (NH) and lncRNA HOTAIR (HOTAIR) could regulate osteoclastic and osteogenic differentiation. This study aimed to explore whether HOTAIR-mediated osteogenic differentiation was regulated by NH.Methods: Steroid-induced osteonecrosis of the femoral head (SONFH) mice model was established. Histopathological changes in mouse osteonecrosis tissues were detected by hematoxylin-eosin staining. Bone marrow stromal cells (BMSCs) were isolated from healthy mice bone marrow samples by Ficoll density gradient and identified by flow cytometry. After treating the BMSCs with NH and dexamethasone or transfecting with HOTAIR overexpression plasmids and siHOTAIR, histone modification of HOTAIR, the cell viability, osteogenic differentiation, and adipogenic differentiation were detected by chromatin immunoprecipitation, MTT, Alizarin Red and Oil Red O staining, respectively. The expressions of HOTAIR and differentiation-related factors in the BMSCs were detected by RT-qPCR and Western blot.Results: HOTAIR was highly expressed in SONFH model mice. NH ameliorated histopathological changes in the model mice, but the effect was reversed by overexpressed HOTAIR. NH increased viability of BMSCs and the H3K27me3 occupancy of HOTAIR, but decreased the expression and the H3K4me3 occupancy of HOTAIR. HOTAIR expression was down-regulated in BMSCs after osteogenic differentiation but was up-regulated after adipogenic differentiation. HOTAIR overexpression inhibited osteogenic differentiation and the expressions of RUNX2, OCN, and ALP, but increased adipogenic differentiation and the expressions of LPL and PPARr in BMSCs; moreover, the opposite results were observed in siHOTAIR.Conclusion: NH ameliorated SONFH by inhibiting the histone modifications of HOTAIR.Keywords: neohesperidin, HOTAIR, bone marrow stromal cells, osteogenesis, adipogenic